EFEKTIVITAS SELF-CONCORDANCE KELUARGA PENGAWAS MINUM OBAT PADA PENCEGAHAN PENULARAN TUBERCULOSIS DI PUSKESMAS DELI TUA - Bahtera Bin David Purba (Jurnal Penelitian Keperawatan Medik, 2019)
The study aims to analyze the effectivity of self-concordance of family members, health officers,teachers, and community leaders as the supervision of taking medication causes tuberculosis. Thistype of research is research quasi-experiment without control. Participants grouped into four drugtakingsupervision groups, namely family, health officers, teachers, and public figures. At thebeginning of the program, each amounted to 40 patients. Supervisors who qualified in the sample arethose who have registered at the Deli Tua Public health center with tuberculosis patients undergoing aminimum of six months of treatment. Data analyzed by illustration ANOVA (one way). The results ofthe study showed self-concordance of different meaningless treatments between family and teachersand community leaders. Self-Concordance control of the environment shows a meaningful differencebetween family with health officers, teachers, and community leaders. Self-concordance control coughor sneezing in this study found to be different meaningful between families with health officers,teachers, and public figures. Recommended to the Health office of Deli Serdang provide training ofcore family members as a supervisor to take medication from the family in the prevention oftransmission tuberculosis